Glomerular filtration rate in children with juvenile idiopathic arthritis - T.P. Borysova; S.V. Samsonenko (Zaslavsky O.Yu., 2022)
Today, it is proved that kidney injury in children with juvenile idiopathic arthritis (JIA) is characterized by a subclinical course and most often remains undiagnosed. One of the main methods to diagnose kidney lesions is determination of estimated glomerular filtration rate (eGFR). The aim of the study was to determine the most optimal method for eGFR evaluation in children with JIA by comparing different calculation methods based on serum creatinine (original Schwartz formula, Counahan-Barratt formula), serum cystatin C (cystatin C-based equation and Hoek formula). Materials and methods. Eighty children with JIA were examined. Serum creatinine level was determined twice (first and third month of study) by the colorimetric kinetic Jaffe reaction, serum cystatin C concentration was evaluated once, in the third month of the study by enzyme immunoassay. We used methods of variation statistics. Results. Parameters of eGFR by cystatin C-based equation 2012 compared to the original Schwartz formula and Counahan-Barratt formula amplified the rate of eGFR disorders by 81.3 % (p < 0.001) and 47.3 % (p < 0.001) in the first month of the study and by 81.3 % (p < 0.001) and 55.0 % (p < 0.001) in the third month, respectively. A similar comparison of the results of Hoek formula with Schwartz and Counahan-Barratt formula showed that according to Schwartz formula, a decrease in the GFR was 41.3 % less frequent (p < 0.001) in both the first and third month. Counahan-Barratt formula in the first study of serum creatinine showed a difference in eGFR compared to Hoek formula by 7.5 % (p < 0.05). During the second study of serum creatinine, the frequency of eGFR reduction according to Counahan-Barratt formula was detected by 15.0 % less often than according to Hoek method (p < 0.09). Conclusions. Changes in renal function differ depending on the formula of eGFR evaluation. The most optimal method to determine eGFR in children with JIA is Hoek formula based on serum cystatin C. In case of limited ability to analyze serum cystatin C, Counahan-Barratt formula based on serum creatinine can be used.